Exploring Learners’ Engagement in A Learner-Generated Content Task Performance - Karimah, Nur Alfin (ICONELT, 2024)
The growing body of research on learners’ engagement in second language acquisition indicates that it is essential to ensure that learners experience meaningful learning. This study investigates how learners are engaged in a learner-generated content task and perceive the assigned assignment. During the course of fifteen minutes, four volunteer Indonesian students who learned English as a foreign language completed a writing task in dyads. At the conclusion of the task, they had to self-rate on a 10-point Likert scale and respond to a post-task exit questionnaire. The quantity of Language Episodes (LREs) (a measure of cognitive engagement), requests for help and responsiveness (measures of social engagement), and laughs (a measure of emotional engagement) were used to gauge their engagement. Results indicated that (1) Learners were more frequently engaged cognitively and socially in a learner-generated content task, and (2) They had positive perceptions of a learner-generated content task. More research is required. Learners at expanding circle country, Indonesia.